An Evaluation of the School Based Curriculum of Suankularb Wittayalai Thonburi Using the CIPP Model - Noinuay, Prajak; Rattanapanya, Sarayut; Diskum, Sucharat (Academic MCU Buriram Journal, 2023)
The purposes of this research were to evaluate the school-based curriculum which concentrates on aspects of context, input, process, and product by using CIPP evaluation model. The samples of 810 were consisted of 5 school administrators, 15 school committees, 108 teachers, 341 students, and 341 parents. The research instruments were questionnaires, and interviewing forms. The data were analyzed by percentage (%), mean ( ), standard deviation (S.D.), and content analysis. The research results found that: The school-based curriculum of Suankularb Wittayalai Thonburi was considered appropriate at the high level. Moreover, regarding to aspects, the aspect of input was considered appropriate at the highest, the aspects of context the aspects of process, and product were considered appropriate at the high level.